A Class I Histone Deacetylase Inhibitor Attenuates Insulin Resistance and Inflammation in Palmitate-Treated C2C12 Myotubes and Muscle of HF/HFr Diet Mice - Lee, Soo Jin; Choi, Sung-E; Lee, Han Byeol; Song, Min-Woo; Kim, Young Ha; Jeong, Jae Yeop; Kang, Yup; Kim, Hae Jin; Kim, Tae Ho; Jeon, Ja Young; Lee, Kwan Woo (Frontiers in Pharmacology, 2020)
Histone deacetylase 3 (HDAC3) inhibitors, which regulate gene expression by inhibiting the deacetylation of histones and nonhistone proteins, have been shown to exert a wide array of biological effects; these include anti-cancer, anti-obesity, and anti-diabetes effects, as well as cardiovascular-protective activity. However, the effects of HDAC3 inhibition on lipotoxicity in C2C12 myotubes and skeletal muscle tissue remain poorly understood. In this study, we investigated the molecular mechanism underlying the protective effect of HDAC3 inhibition under lipotoxic conditions, i.e., in palmitate (PA)-treated C2C12 myotubes and skeletal muscle tissue in high fat (HF)/high fructose (HFr) diet mice. PA treatment of C2C12 myotubes increased HDAC3 protein expression and impaired mitochondrial oxidation, resulting in increased mitochondrial ROS generation and an accumulation of intracellular triglycerides (TG). Prolonged exposure led to increased inflammatory cytokine expression and insulin resistance. In contrast, MS-275, a class I HDAC inhibitor, dramatically attenuated lipotoxicity, preventing PA-induced insulin resistance and inflammatory cytokine expression. Similar beneficial effects were also seen following HDAC3 knockdown. In addition, MS-275 increased the mRNA expression of peroxisome proliferator activator receptor γ-coactivator 1α (PGC1α) and mitochondrial transcription factor A (TFAM), which serve as transcriptional coactivators in the context of mitochondrial metabolism and biogenesis, and restored expression of peroxisome proliferator-activated receptor alpha (PPARα), medium-chain acyl-coenzyme A dehydrogenase (MCAD), enoyl-CoA hydratase, and 3-hydroxyacyl CoA dehydrogenase (EHHADH). In vivo, treatment of HF/HFr-fed mice with MS-275 ameliorated insulin resistance, stress signals, and TNF-α expression in gastrocnemius muscle. Taken together, these results suggest that induction of HDAC3 inhibition by MS-275 protects against lipotoxicity in C2C12 myotubes and skeletal muscle, and may be effective for the treatment of obesity and insulin resistance.